PENGARUH PESAN IKLAN SLO DENGAN SIKAP KHALAYAK TERHADAP KEINGINAN MEMBUAT SLO - Windhi Tia Saputra; Witanti Prihatiningsih (Dialektika, 2017)
This research discusses about the public service announcements message from the Ministry of Energy and Mineral Resources (ESDM). Subject of this research is Sertifikat Laik Operasi (SLO) advertisement. The purpose of this study was to determine the effect of SLO advertising messages exposure with public attitudes towards the desire to apply SLO. This study uses a quantitative method with linear regression analysis. The population in this study were active students of FISIP UPN "Veteran" Jakarta, with total 1,202 students. By using Slovin purposive sampling techniques and formulas, it results in a sample size of 92 students. The theory used in this research is the theory of cognitive response. Based on the result data collected, there is a significant and strong relationship between advertising messages SLO with public attitudes towards the desire to apply SLO. Also, SLO advertising messages has an influence on the attitude of the public desire to apply SLO.